2014
DOI: 10.1002/app.41155
|View full text |Cite
|
Sign up to set email alerts
|

Renewable thermoset copolymers from tung oil and natural terpenes

Abstract: The cationic copolymerization of tung oil, limonene, and myrcene as comonomers, initiated by boron trifluoride, is presented and discussed in this work. Dynamic mechanical analysis revealed that all copolymers behave as thermosets. FTIR spectra for both copolymers, after extraction with dichloromethane, suggested that the major component of the insoluble fraction was reacted tung oil (a cross‐linked triglyceride network). Likewise, unreacted tung oil was found to be the main component of the soluble phase. Als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Polymyrcene has similar dynamic mechanical properties to natural rubber, but the modulus values at its rubbery plateau are still too low to consider polymyrcene as a replacement for natural rubber in applications at room temperature. One option is to increase the modulus through copolymerization of myrcene with stiffness monomers, such as styrene or other renewable monomers . Nevertheless, results are promising for developing renewable elastomers with optimal properties and for producing rubber formulation, adhesive, or plastics modifiers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymyrcene has similar dynamic mechanical properties to natural rubber, but the modulus values at its rubbery plateau are still too low to consider polymyrcene as a replacement for natural rubber in applications at room temperature. One option is to increase the modulus through copolymerization of myrcene with stiffness monomers, such as styrene or other renewable monomers . Nevertheless, results are promising for developing renewable elastomers with optimal properties and for producing rubber formulation, adhesive, or plastics modifiers.…”
Section: Resultsmentioning
confidence: 99%
“…One option is to increase the modulus through copolymerization of myrcene with stiffness monomers, such as styrene or other renewable monomers. [49] Nevertheless, results are promising for developing renewable elastomers with optimal properties and for producing rubber formulation, adhesive, or plastics modifiers.…”
mentioning
confidence: 99%
“…It has been shown that these reactions result in highly crosslinked polymer networks [12][13][14][15]. Likewise, tung oil has been used as a key component in cationic bio-based thermosets by crosslinking it with limonene and myrcene [16]. Tung oil has also been used in more straight-forward applications, such as protecting coatings for wood surfaces [17], and protein films [18], or as a strengthening additive for unsaturated polyester resins [19].…”
Section: Introductionmentioning
confidence: 99%
“…Shibata and Asano reported the preparation of biobased thermosetting polymers by the reaction of maleimides with myrcene and limonene. The cationic copolymerization of tung oil, limonene, and myrcene as comonomers is also reported in the literature . Wang et al .…”
Section: Sustainable Rubbers and Rubber Like Materialsmentioning
confidence: 74%